Protecting Mammalian Hair Cells from Aminoglycoside-Toxicity: Assessing Phenoxybenzamine’s Potential - Majumder, Paromita; Moore, Paulette A.; Richardson, Guy P.; Gale, Jonathan E. (Frontiers in Cellular Neuroscience, 2017)
Aminoglycosides are widely used antibiotics because of their low cost and high efficacy against gram-negative bacterial infection. However, aminoglycosides are ototoxic, causing the death of sensory hair cells in the inner ear. Strategies aimed at developing or discovering agents that protect against aminoglycoside ototoxicity have focused on inhibiting apoptosis or more recently, on preventing antibiotic uptake by the hair cells. Recent screens for ototoprotective compounds using the larval zebrafish lateral line identified phenoxybenzamine as a potential protectant for aminoglycoside-induced hair cell death. Here we used live imaging of FM1-43 uptake as a proxy for aminoglycoside entry, combined with hair-cell death assays to evaluate whether phenoxybenzamine can protect mammalian cochlear hair cells from the deleterious effects of the aminoglycoside antibiotic neomycin. We show that phenoxybenzamine can block FM1-43 entry into mammalian hair cells in a reversible and dose-dependent manner, but pre-incubation is required for maximal inhibition of entry. We observed differential effects of phenoxybenzamine on FM1-43 uptake in the two different types of cochlear hair cell in mammals, the outer and inner hair cells. The requirement for pre-incubation and reversibility suggests an intracellular rather than an extracellular site of action for phenoxybenzamine. We also tested the efficacy of phenoxybenzamine as an otoprotective agent. In mouse cochlear explants the hair cell death resulting from 24 hours exposure to neomycin was steeply dose-dependent, with 50% cell death occurring at 230 µM for both inner (IHC) and outer hair cells (OHC). We used 250 µM neomycin in subsequent hair-cell death assays. At 100 μM with 1 hour pre-incubation, phenoxybenzamine conferred significant protection to both IHCs and OHCs, however at higher concentrations phenoxybenzamine itself showed clear signs of ototoxicity and an additive toxic effect when combined with neomycin. These data do not support the use of phenoxybenzamine as a therapeutic agent in mammalian inner ear. Our findings do share parallels with the observations from the zebrafish lateral line model but they also highlight the necessity for validation in the mammalian system and the potential for differential effects on sensory hair cells from different species, in different systems and even between cells in the same organ.